Electronic Medical Record User Satisfaction Using the End User Computing Satisfaction (EUCS) Method Approach at Diana Permata Medika Clinic in 2026 - Inna Sholihati Embrik; Andre Prantino Depeda; Sahrul Rudiyansah (International Journal of Health Engineering and Technology, 2026)
User satisfaction in the implementation of electronic medical records greatly affects the effectiveness of health information systems. User satisfaction is the overall level of satisfaction of health workers with their interactions with electronic medical records. This study aims to evaluate user satisfaction with electronic medical records based on the EUCS method, which covers the dimensions of content, accuracy, display, ease of use, and timeliness at the Diana Permata Medika Clinic in 2026. This descriptive study involved 37 respondents selected through purposive sampling. The research instrument was a user satisfaction questionnaire based on the EUCS method with a Likert scale. Data analysis used univariate analysis. The results showed that the satisfaction percentage for content was 85.14%, accuracy 84.59%, display 82.01%, ease of use 81.85%, and timeliness 82.84%. All dimensions reached the “Very Good” category. The clinic is expected to maintain and continue to improve its electronic medical record services through regular training programs for health workers.